Shanghai Gone: Domicide and Defiance in a Chinese Megacity - Shao, Qin (Rowman & Littlefield Publishers, 2013)
Shanghai has been demolished and rebuilt into a gleaming megacity in recent decades, now ranking with New York and London as a hub of global finance. But that transformation has come at a grave human cost. This compelling book is the first to apply the concept of domicide—the eradication of a home against the will of its dwellers—to the sweeping destruction of neighborhoods, families, and life patterns to make way for the new Shanghai. Here we find the holdouts and protesters, men and women who have stubbornly resisted domicide and demanded justice. Qin Shao follows, among others, a reticent kindergarten teacher turned diehard petitioner; a descendant of gangsters and squatters who has become an amateur lawyer for evictees; and a Chinese Muslim who has struggled to recover his ancestral home in Xintiandi, an infamous site of gentrification dominated by a well-connected Hong Kong real estate tycoon. Highlighting the wrenching changes spawned by China’s reform era, Shao vividly portrays the relentless pursuit of growth and profit by the combined forces of corrupt power and money, the personal wreckage it has left behind, and the enduring human spirit it has unleashed. To see the author's blog post on Asia Society, please click here.